EDUCATION AUTHORITY, FUNDS AND ACCOUNTABILITY - Dalmi Iskandar Sultani; Amiruddin Siahaan; Muhammad Adyan Simanjuntak; Syarifuddin; Surianto (Sensei International Journal of Education and Linguistic, 2021)
Education depends on funds or funding, and quality education requires high funds or costs; it is impossible to want quality education at low costs. Good and quality Education if the accountability of Education is carried out correctly. This study attempts to describe the authority, funding, and accountability of Education. They use the library method with literature research tools, books, and manuscripts. The study results explain that authority means power, the authority given, entrusted by the state. Authority is a position, right, authority to ratify. Authority is obtained from two attributive and non-attributive ways. Education funds are expenditures in the form of resources in goods/objects; money is intended to support the learning process. Accountability is accountability and is divided into two vertical accountability and horizontal accountability. Educational accountability means independent, continuous learning outcomes assessment: success, professional, and system accountability. Accountability involves the task of individuals/organizations who are obliged to take responsibility for their duties, work, whether given sanctions or rewards. In conclusion, if the authority, funding, and accountability of Education are carried out properly, it will make an educational institution of good quality. On the other hand, it will be difficult and will never even be able to advance and have quality education. Sustainable learning outcomes. Success, professional, and system accountability. Accountability involves the task of individuals/organizations who are obliged to take responsibility for their duties, work, whether given sanctions or rewards. In conclusion, if the authority, funding, and accountability of Education are carried out properly, it will make an educational institution of good quality. On the other hand, if not, it will be difficult and will never even be able to advance and have quality education. Sustainable learning outcomes. Success, professional, and system accountability. Accountability involves the task of individuals/organizations who are obliged to take responsibility for their duties, work, whether given sanctions or rewards. In conclusion, if the authority, funding, and accountability of Education are carried out properly, it will make an educational institution of good quality. On the other hand, it will be difficult and will never even be able to advance and have quality education